Photoluminescent and photocatalytic behaviour of zinc oxide nanostructures synthesized through the room temperature ultrasonication method. (24th August 2022) - Malik, Khurshaid Ahmad; Malik, Javied Hamid; Assadullah, Insaaf; Tomar, Radha
Abstract: In the present article we report the synthesis of zinc oxide (ZnO) nanostructures at room temperature using an ultrasonication technique to study their photoluminescent and photocatalytic behaviour. Synthesized nanomaterial showed a strong near band edge ultraviolet (UV) light emission and red emission, thereby finding its use in photoluminescent materials. We developed a UV/ZnO/O2 /H2 O2 system for the photodegradation of organic pollutants in an aqueous system. We used synthesized nanostructures to photodegrade phenol red (PR) dye to check their photocatalytic activity. The ZnO nanostructures photodegraded more than 90% of the PR dye under UV light irradiation in which photonic energy is converted to chemical energy (photocatalytic energy conversion), thereby exploitable for water purification applications. Synthesized ZnO nanostructures were characterized using powder X‐ray diffraction, Fourier transform infrared spectroscopy, UV–visible light spectroscopy, scanning electron microscopy, and energy dispersive X‐ray spectroscopy to investigate their structural, optical, morphological, and compositional properties, respectively. Abstract : Highly crystalline synthesized ZnO nanostructures found their way into photoluminescent materials like LCDs, LEDs, phosphors, and sensors and were used as a source of red emission in lighting applications. The nanomaterial showed high photocatalytic activity using a UV light‐driven photocatalytic reactor and was analyzed by a UV‐visible spectrophotometer.